2020
DOI: 10.1136/jitc-2020-000586
|View full text |Cite
|
Sign up to set email alerts
|

Granzyme B is correlated with clinical outcome after PD-1 blockade in patients with stage IV non-small-cell lung cancer

Abstract: BackgroundA minority of patients with advanced non-small-cell lung cancer (NSCLC) benefit from treatment with immune checkpoint inhibitors (ICIs). Ineffective effector function of activated T and NK cells may lead to reduced tumor cell death, even when these activated effector cells are released from their immune checkpoint brake. Hence, in this study we aimed to assess the association of baseline serum granzyme B, as well as germline variation of theGZMBgene, with clinical outcome to programmed cell death pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 37 publications
1
38
0
Order By: Relevance
“…As observed previously in patients with non-small cell lung cancer (NSCLC) [36], patients with heterozygous or homozygous variation of GZMB c.128C > A have significantly worse PFS and OS after anti-PD-1 monotherapy in univariable analysis. After correction for baseline characteristics, however, these associations did not retain significance.…”
Section: Discussionsupporting
confidence: 68%
“…As observed previously in patients with non-small cell lung cancer (NSCLC) [36], patients with heterozygous or homozygous variation of GZMB c.128C > A have significantly worse PFS and OS after anti-PD-1 monotherapy in univariable analysis. After correction for baseline characteristics, however, these associations did not retain significance.…”
Section: Discussionsupporting
confidence: 68%
“…Granzyme-B, the granule protease secreted by NK and CD8 + T cells, induces apoptosis through BAX/BAK-mediated mitochondrial apoptotic pathway [ 47 ]. The increased level of granzyme-B in serum or tumor was correlated with favorable outcomes in patients with colorectal cancer or NSCLC [ 48 , 49 ]. In our results indicated the combination group presented significantly higher expression of granzyme-B and apoptotic proteins (BAX and cleaved-caspase-3) in CT-26 or B16-F10 tumor tissues compared to hIL15-ABD or anti-PD-L1 therapy ( Figure 5 I–K and Figure 4 N–P).…”
Section: Discussionmentioning
confidence: 99%
“…Many immunotherapeutic drugs including CTLA-4 and PD-1 inhibitors eliminate cancer cells by increasing IFN γ expression. Hurkmanns et al found that lower granzyme B levels in patients with metastatic cancer favored tumor growth by halting the antitumor immunity response by cytotoxic immune cells ( Hurkmans et al, 2020 ). Co-stimulatory molecules such as CD86 which are expressed on mature DCs are critical in the activation of naïve T cells ( Hubo et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%